The Significance of ‘Integuments’ in John 10:10 and Genesis 3:21 - Sitepu, Edward; Sembiring, Milisi; Muanley, Yonas; Sigalingging, Abraham Barlian (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
This paper aims to explore the promise that will be fulfilled in Jesus based on Genesis 3 verse 15. descriptive qualitative research to solve the problems of the study. The method used is to provide a textual explanation of God’s temporary, emergency and imperfect actions in a theological-style material. The OT text regarding God's actions contained in Gen. 3:21 is of an emergency nature. Meanwhile, if the NT text in John 10:10 is divided into 10 a and 10 b, it indicates Jesus' mission for humans who have sinned and must face the rulers of this world. Two facts, where the emergency action of God YHWH and the complete fulfillment of Jesus' task as a form of fulfillment of God's promise to the first humans require a precise explanation and how this emergency action is related to its fulfillment. In this problem, the approach uses a comparative approach to these two facts to then confirm the key words (underlying text) in Gen. 3:21 and John 10:10 a and 10 b. The results show that the fulfillment of Jesus' task was the fulfillment and at the same time permanently overcoming this emergency action.